A sustainable approach to dairy wastewater treatment through electrocoagulation: From beverage cans to clean water - Nosa Idusuyi; Marzouq Adeyemi Adebayo; Chinenye Adaobi Igwegbe; Orhadahwe Thomas Aghogho; Anina James; Rasaq Adebayo Kazeem (Waste Management Bulletin)
Dairy industry wastewater, laden with high levels of biological oxygen demand (BOD), chemical oxygen demand (COD), and various pollutants, poses significant environmental concerns. This study introduces the innovative use of recycled aluminium cans as electrodes for electrocoagulation, presenting an eco-friendly and cost-effective approach to wastewater treatment that aligns with circular economy principles. This study explores the efficacy of electrocoagulation (EC) in treating dairy wastewater, focusing on the influence of treatment duration, voltage, and pH levels on BOD, COD, and turbidity reduction. Utilizing recycled aluminium electrodes derived from beverage cans, a Taguchi design of experiments with a 3-factor, 3-level orthogonal array was employed. Results from nine experiments reveal that higher voltages and alkaline pH levels notably enhanced COD and BOD removal efficiencies. For instance, high removal rates of 91.67 % for COD and 95.36 % for BOD were achieved at 20 V and pH 9 over a 15-minute treatment duration were obtained from experiments. Furthermore, optimal overall EC performance parameters were obtained using Taguchi and Multi-response optimization using TOPSIS. Analysis of turbidity removal efficiencies demonstrates the significant impact of voltage and treatment duration. The study provides valuable insights into optimizing electrocoagulation processes for efficient treatment of dairy wastewater, offering a sustainable solution for environmental preservation and resource recovery.